A high precision scheme for micro‐channel processing in quartz glass using femtosecond laser. Issue 8 (August 2017) - Zhang, Pan; Chen, Lei; Wang, Fubing; Tu, Paul
Abstract: Ultra‐short pulse laser with unique advantages in micromachining, especially on the hard brittle material becomes the focus of study on micro‐structure processing. Theoretical and experimental researches are taken from the ablation properties of micro‐channel in the quartz glass by femtosecond laser. As the ablation depth of quartz glass has not relationship obviously with defocusing distance within LAV effective range, a new way to control precisely the ablation depth of quartz glass is present in the study. With fixed laser power, the ablation depth could be known easily by the length of the ablation streak while moving the femtosecond laser focus along the straight line with a 45‐degree angle from the quartz glass surface within the LAV range. Research is carried out to study laser pulse power, scanning velocity and step distance to do something with micro‐channel ablation quality. According to the parameters of test, the micro‐channel with rectangle cross section of the quartz glass is processed, and then we analyze the ablation morphology and processing efficiency. The results provided a important suggestion to process micro‐structure precisely for quartz glass by femtosecond laser.